Post-communism, liberalism and solidarity in the countries of central and eastern Europe after 1989 - Andrzej Kobyliński (The Francis de Sales Scientific Society (TNFS.PL), 2019)
The main aim of this article is to analyze the transition from communism to post-communism in Eastern Bloc countries after 1989. Post-communism in Central and Eastern Europe gradually transformed into various forms of democracy. The political project implemented in post-communist societies is a selective kind of liberalism, which entailed a number of negative consequences. Unfortunately, in the process of transition from post-communism to liberal democracy, a very small role was played by the category of solidarity as an important virtue of social life. We need today a global expansion of solidarity as a new worldwide ethos.